O uso da simulação realística no ensino de transporte intra-hospitalar para graduandos de Enfermagem - Santana, Ellen Reis [UNIFESP] (2019)
Aim: To build and validate a scenario to simulate the intra-hospital transportation of critical patients and to analyze the simulation as a teaching strategy for students of the undergraduate nursing course. Methods: A methodological study to build and validate a simulation scenario to teach intra-hospital transportation and, an analytical cross-sectional study with a quantitative approach to assess the execution of the validated scenario. In the first phase of the study, the scenario was built based on the literature about the theme, and after, it was validated by five specialists using the Delphi technique the level of agreement of 80%. In the second phase, applications of the validated scenario were conducted as the assessment of the simulation design, students’ experiences with the debriefing, students’ satisfaction and, the self-confidence related to learning with the simulation. Results: A scenario containing 26 topics was developed to be assessed regarding the pertinence, clarity, objectivity, feasibility, actual content, vocabulary and a field for observations. Between the specialists, the majority was female (80%), with a mean age of 43 years; 80% had a Doctoral degree, all had health-related training, participated in an instructor’s course, with a mean experience of 9.6 years in teaching clinical simulations. Two assessments were needed from specialists to reach an 80% agreement, and the topics that needed adjustments were related to the case description, and duration of the simulated activity. To apply the scenario, the sample was composed by 74 students; mean age of 23.5 (20 – 36) years (n = 74); predominance of females (89.2%), 33.8% had professional experience, the majority as an intern (73.1%) in many sectors. The design simulation analysis demonstrated that all students (100%) totally or partially agreed that the simulation was adequate for their specific level of knowledge and ability, the constructive feedback and simulation allowed to analyze their behavior and the conducted actions, and 95.9% totally or partially agreed that the scenario was similar to a real-life situation. When analyzing the debriefing experience, most students agreed (86.5%) that this moment helped to organize their thoughts and their questions were answered (89.2%). Additionally, 94.6% of participants reported the debriefing as a learning opportunity, and the professors adequately clarified issues. Regarding the students’ learning satisfaction and self-confidence, 90.5% of students totally agreed that the used teaching method was useful and effective, 89% of students totally agreed that the professor used useful resources to teach the simulation and the majority of students demonstrated self-confidence in the content presented in this simulation; 97.3% of students totally or partially agreed with this affirmation. Conclusion: In this study, the construction and validation of a scenario to teach intra-hospital transportation were successfully conducted, which should be used in many services to demonstrate the real impact in the training of nursing students and in professional enhancement. The scenario design was considered adequate to teach intra-hospital transportation of critical patients, most students were able to identify the importance of the experience with the debriefing in the learning consolidation and they were satisfied and self-confident after the simulation.